Penentuan Waktu Pembangunan Pabrik Semen Baru untuk Antisipasi Shortages di Indonesia - Saputra, Yudha Andrian (Jurnal Manajemen Teknologi, 2011)
The capacity expansion through a new plant is a strategic issue for cement industry. Determining the right time for expansion is a critical issue since built too fast means the cement manufacturer will facing overproduction risks, while too slow the cement manufacturer may lose their potential markets. We discuss the situation dealt by cement industry to determine when this industry requires additional capacity. We use the concept of equilibrium supply-demand to develop a surplus/shortages map of Indonesian cement industries. The result indicates that the cement industry will experience shortages in 2014 with quantity around 397 thousands tons (for 90% utilization assumption). Development of new cement plant should be started from 2011 with an assumption it require 3 years construction period.Keywords: the equilibrium of supply-demand, shortages, the capacity expansion, cement industry